Research on the Impact of Customer Participation in Virtual Community on Service Innovation Performance— The Role of Knowledge Transfer - Wang, Jianhua (Frontiers in Psychology, 2022)
Internet technology has given birth to continuous changes in business model and format innovation. With increasingly critical consumers, blowout development model and format innovation, enterprises are increasingly aware of the importance of customer participation in service innovation. At the same time, the development of information technology provides convenient conditions for communication between enterprises and customers, and online virtual community also provides a platform for customers to participate in the process of enterprise service innovation in an instant. Based on the theory of customer participation, knowledge transfer and service innovation performance, this paper explores the influence mechanism of customer participation in virtual community on service innovation performance, and analyzes the mediating role of knowledge transfer. Through the analysis of the results of the questionnaire, the relevant hypotheses are verified. The results show that customer participation in virtual community has a positive impact on service innovation performance. Customer participation helps enterprises obtain relevant knowledge such as customer needs and reduce barriers to knowledge sharing. In addition, enterprises will acquire customer knowledge about new products, which provides the possibility for the development of new products and services, thereby enhancing the enterprises’ service innovation performance. Knowledge transfer plays a part of mediating role between customer participation and service innovation performance. In the process of enterprises’ service innovation, customers mainly participate in the enterprise by means of knowledge transfer and help the enterprise improve service innovation performance.